2024
DOI: 10.1063/5.0187795
|View full text |Cite
|
Sign up to set email alerts
|

Research on ionization characteristics of atmospheric pressure pulse-modulated microwave He/air plasma jet

Lu Zhang,
Zhaoquan Chen,
Binbin Chu
et al.

Abstract: The atmospheric pressure pulsed microwave He plasma jet has the advantages of high electron density and abundant active particles, but its shrinking on the discharge electrode morphology limits its application range. In order to modulate a He plasma jet with a longer plume and study its ionization development characteristics, we constructed a dual-channel pulsed microwave coaxial discharge device. He and air were, respectively, injected into the inner and outer gas channels of the resonator to generate a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Duty cycle in plasma jets is controlled by the pulse width modulation (PWM) technique to regulate the on-off cycling of the plasma jet using either a pulsed direct current (DC) output (for DC power supplies) or a continuous alternating current (AC) waveform with pulsed modulation (for AC power supplies). Several studies have reported the use of radio-frequency (RF) pulse modulation and microwave (MW) pulse modulation to operate plasma jets [35][36][37][38][39][40]. In these studies, it was shown that RF plasma jets operated below 50% duty cycle, enhance air entrainment into the plasma ionization region because operating at lower duty cycles cools down the plasma more between pulses, leading to a higher temperature gradient that can create stronger convective flow between the plasma and the ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…Duty cycle in plasma jets is controlled by the pulse width modulation (PWM) technique to regulate the on-off cycling of the plasma jet using either a pulsed direct current (DC) output (for DC power supplies) or a continuous alternating current (AC) waveform with pulsed modulation (for AC power supplies). Several studies have reported the use of radio-frequency (RF) pulse modulation and microwave (MW) pulse modulation to operate plasma jets [35][36][37][38][39][40]. In these studies, it was shown that RF plasma jets operated below 50% duty cycle, enhance air entrainment into the plasma ionization region because operating at lower duty cycles cools down the plasma more between pulses, leading to a higher temperature gradient that can create stronger convective flow between the plasma and the ambient air.…”
Section: Introductionmentioning
confidence: 99%